CONSUMER DEMAND THEORY IN MACROECONOMICS AND ITS APPLICATION IN MARKETING RESEARCH (Marketing Journal, 2025)
The article covers the theory of consumer demand as an object of macroeconomic analysis and proves the limitations of its use in conducting marketing research.
Keywords: consumption; disposable income; marginal propensity to consume; consumption function; relative income theory; life cycle theory; Snob effect; Veblen effect